1974
DOI: 10.1149/1.2401812
|View full text |Cite
|
Sign up to set email alerts
|

Amalgam Decomposition

Abstract: The rate of amalgam decomposition in a laboratory tower decomposer with 40% normalNaOH was measured at 80°C in dependence on concentration and rate of flow of the amalgam. The dependence of the reaction rate on the rate of flow shows a maximum, which was explained theoretically and the constants in the equation for the rate of decomposition were evaluated. The bed material consists of graphite balls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…H -----0.087251 --ST Hence, the tower height for the given parameters (cNa,i ~ 0.2; cNa,2 ~ 0.01) is equal to 82.2 cm in good accord with the experiment (15). It follows that the parameters used in the calculation will be close to those obtained from experimental data.…”
Section: F]] Dcnasupporting
confidence: 70%
See 1 more Smart Citation
“…H -----0.087251 --ST Hence, the tower height for the given parameters (cNa,i ~ 0.2; cNa,2 ~ 0.01) is equal to 82.2 cm in good accord with the experiment (15). It follows that the parameters used in the calculation will be close to those obtained from experimental data.…”
Section: F]] Dcnasupporting
confidence: 70%
“…Equation [48] was verified by measurement of the dependence of the decomposition rate on amalgam concentration at constant rate of flow of the amalgam through the tower as well as by measurement of the decomposition rate on the rate of flow at constant amalgam concentration (15).…”
Section: Drop Model For Amalgam Decompositionmentioning
confidence: 99%
“…The erosion of graphite packing leads to decrease in the efficiency of decomposer owing to severe alteration in the local rates of amalgam decomposition reaction over significant period of time. For caustic concentration of about 37.4% (w/w) and fixed bed temperature of 80°C, Rajasekaran et al observed that on average, the decomposition rates after one and half year operation are 15% to 20% lower than those after 1 month operation 7 . Graphite erosion generates internal hotspots in fixed bed and bypassing of concentrated amalgam.…”
Section: Introductionmentioning
confidence: 99%
“…For caustic concentration of about 37.4% (w/w) and fixed bed temperature of 80 C, Rajasekaran et al observed that on average, the decomposition rates after one and half year operation are 15% to 20% lower than those after 1 month operation. 7 Graphite erosion generates internal hotspots in fixed bed and bypassing of concentrated amalgam. Eroded graphite forms slurry in electrolyte solution and this slurry formation leads to abrupt changes in local heat and mass transfer coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…In preceding communications (1,2), the problem of calculating the decomposition rate of sodium amalgam in a tower reactor filled with graphite balls was treated. It followed that the reaction rate is directly proportional to the specific surface area of the bed (in cm2/cm 8 of bed).…”
mentioning
confidence: 99%